Management of childhood vitiligo − a brief review - Sahana P Raju; Sumit Kaur; Eswari Loganathan (Wolters Kluwer Medknow Publications, 2022)
Vitiligo comprises of one of the commonest reasons for a dermatology consultation in the pediatric age group, worldwide. The incidence of childhood vitiligo varies from 1% to 8%, making it a significant pediatric condition. Various theories have been put forward to explain the occurrence of depigmentation in vitiligo, of which genetic factors play a predominant role in childhood vitiligo. The various modalities of treatment of childhood vitiligo are reviewed in this article. The management of vitiligo is extremely challenging, more so in the pediatric age group, as it can lead to significant psychologic trauma and dysregulation of social development in a child. The goals of management of childhood vitiligo should be aimed at addressing all these issues and achieving an optimum result out of the available modalities.